Передопераційна гормональна терапія місцево поширеного раку молочної залози - Щепотін, І. Б.; Зотов, О. С.; Анікусько, М. Ф.; Любота, І. І.; Любота, Р. В. (Clinical Endocrinology and Endocrine Surgery, 2011)
Endocrine therapy for locally advanced breast cancer (LABC) has more than a100-year history. Efficiency of its use in adjuvant therapy confirmed by the results of many randomized trials, however, as neoadjuvant antihormonal drug therapy induction drugs are rarely used. The results of many randomized trials on the efficacy of neoadjuvant hormonal ER + and/or ER + breast cancer in postmenopausal women indicate a high response rate from the tumor which allows to achieve objectives neoadjuvant therapy in 40-60% of patients. Optimal drugs for neoadjuvant hormonotherapy are aromatase inhibitors of the third generation (letrozole, anastrozole, exemestane) daily for 3-4 months. Preoperative endocrine therapy development aimed at identifying additional factors (besides the presence of ER and/or RP) which define a positive response from the tumor to treatment and individualize this treatment and maximize clinical outcomes.